Separation of microalgae cultivated in anaerobically digested black water using Moringa Oleifera Lam seeds as coagulant - Silva, Débora Fernanda Santos [UNESP]; Speranza, Lais Galileu [UNESP]; Quartaroli, Larissa [UNESP]; Moruzzi, Rodrigo Braga [UNESP]; Silva, Gustavo Henrique Ribeiro [UNESP] (Elsevier, 2021)
The main aim of this work was to evaluate the efficiency of Moringa oleifera Lam (MOL) integral powder as a natural coagulant for the harvesting of microalgae cultivated in anaerobically digested black water (AnBW) and to evaluate the microalgae's characteristics for its application as an organic fertilizer. The use of 475 mg L−1 of MOL as coagulant with 45 min for sedimentation (settling velocity of 0.17 cm min−1) at pH value of 7 presented high efficiency in removing turbidity (93 %), optical density (90 %), true color (38 %), total suspended solids (58 %), chemical oxygen demand (53 %), nitrogen (57 %) and phosphorus (60 %). The microalgae biomass harvested from the process has the potential to be applied as fertilizer as presented characteristics (nutrients amount) comparable to other organic fertilizers available on the market.
Keywords: Coagulation; Fertilizer; Microalgae; Moringa oleifera Lam seeds; Wastewater treatment